The Effect of Cooperative Learning Type Student Teams Achievement Division (STAD) on Understanding Mathematical Concepts in Class VIII Students of MTs N Pekanbaru - Putri Wahyuni (International Journal of Trends in Mathematics Education Research, 2019)
This study starts from the problem of the low understanding of the mathematical concepts of MTs N Pekanbaru students. This can be seen in the results of tests of understanding mathematical concepts obtained by students. To overcome this problem, STAD type cooperative learning is used. The purpose of this study was to determine the effect of the STAD type cooperative learning model on understanding the mathematical concepts of class VIII MTs N Pekanbaru students. This type of research is Quasi Experiment. The population in this study were Pekanbaru MTs N students. The sample in this study was class VIII MTs Simpang Tiga Pekanbaru as an experimental class and class VIII MTs N Muara Fajar Pekanbaru as a control class randomly selected. The instrument used is a written test regarding understanding students' mathematical concepts. The data obtained were analyzed using the t test, Mann-Whitney U test. The results showed that (1) understanding of mathematical concepts students taught by STAD type cooperative learning was higher than students who were taught using conventional learning, (2) understanding students' mathematical concepts high initial ability taught by STAD type cooperative learning is higher than high initial capable students taught with conventional learning, and (3) understanding mathematical concepts of low initial ability students taught by STAD type cooperative learning is higher than low initial ability students taught with conventional learning.